THE INFLUENCE OF BRAND IMAGE, PRICE PERCEPTION, AND SERVICE QUALITY ON CUSTOMER’S LOYALTY OF “POS EXPRESS” WITH CUSTOMERS’ SATISFACTION AS INTERVENING VARIABLE (A CASE STUDI AT SEMARANG PROCESSING CENTRE) - Astrid Tiara Murti; Budi Prasetya; Isnaini Nurkhayati (JOBS (Jurnal Of Business Studies), 2017)
This study aims to identify and analyze the influence of brand image, price perception, and service quality on customer’s loyalty of Pos Express with customers’ satisfaction as intervening variable. This study is counted as research survey, the population in this study is the customer who had used Pos Express more than twice. The technique used for collecting the data is purposive sampling, with obtained sample as many as 100 people. The research instrument used in this study has been tested it’s validity and reliability. The data analysis tools used for research hypotheses is path analysis with helps from multiple linear regression and sobel test. The result of first regression model shows that there are two independent variables which is significant on customers’ satisfaction partially and one was not. Price perception variable has the most influence on Pos Express customers’ satisfaction. The value of coefficient determination R2 is 0.205, which means that all independent variables ability to explain the variance on Pos Express customers’ satisfaction variable is 20.5%, and the rest can be explained by other variables that not included in this research. The result of second regression model shows that there are four independent variables affect customer’s loyalty partially and simultaneously. Price perception has the most influence on Pos Express customer’s loyalty. The value of coefficient detemintion R2 is 0.579, which means that all independent variables ability to explain the variations on Pos Express customer’s loyalty variable is 57.9%, and the rest can be explained by other variables that not included in this study. According to the result of sobel test, partially price perception and service quality have significant indirect effect on customer’s loyalty of Pos Express through customers’ satisfaction. While brand image doesn’t has indirect effect on customer’s loyalty through customers’ satisfaction.